Determination of geomechanical parameters using a KBS system and application to an underground station - Miranda, Tiago F. S. (2005)
In this paper a KBS computational system, designated by GEOPAT, for the calculation of geomechanical parameters for modelling underground structures in rock and soil formations is presented. To congregate the specialists' knowledge in rock and soil domains, and in particular in the tunnel engineering, causal nets have been established for decision support. GEOPAT determines the parameters for rock and soil formations, as well as heterogeneous rock formations. The developed GEOPAT system was applied to a large underground station in urban environment, excavated in granite formations, in order to obtain the deformability and strength parameters of the surrounding rock masses. Numerical models were developed considering either the obtained geomechanical parameters using artificial intelligence techniques or the parameters used in design. The numerical results obtained with the two sets of parameters are compared, as well as with the monitoring results. Some conclusions are drawn.